English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-11-02 03:29:10 · 18 answers · asked by Tk 2 in Science & Mathematics Mathematics

18 answers

4469

2006-11-02 03:32:42 · answer #1 · answered by lisa 5 · 0 1

2+2(67+78)30-1 = 2 + (2*145*30) - 1
= 1 + (290*30)
= 1 + 8700
= 8701

2006-11-02 13:02:32 · answer #2 · answered by Akilesh - Internet Undertaker 7 · 0 0

The order of priority among the operations in solving an expression is given by BEDMAS rule.
The order of priority is
* Bracket
* Exponential
* Division
* Multiplication
* Addition
* Subtraction

Solving the above expression in that order gives the correct result.

2+2(67+78)30-1
= 2+2(145)30-1 ' First solving the bracket
= 2+2*4350-1 ' Solving one multiplication
= 2+8700-1 ' Solving the other multiplication
= 8702-1 ' Next addition
= 8701 ' At last subtraction

Thus u could solve it
Hope u got wat u wanted

2006-11-02 03:43:36 · answer #3 · answered by Arun R 2 · 0 0

8701, because 67+78 = 145, 145 x 2 x 30 = 8700, 8700 + 2 - 1 = 8701

2006-11-02 03:31:42 · answer #4 · answered by just.ride 1 · 0 0

2+2(67+78)30-1
2+2*145*30-1=2+8700-1=8701

2006-11-02 05:09:32 · answer #5 · answered by yupchagee 7 · 0 0

2+2(67+78)30-1=
2+2(145)30-1=
2+2*4350-1=
2+8700-1
8702-1=8701

so the answer is 8701.

hope this helps :)

2006-11-02 03:48:50 · answer #6 · answered by good day :) 2 · 0 0

2+2(145)30 - 1
= 2+60(145) - 1
= 2+ 8700 - 1
= 8702 - 1
= 8701

2006-11-02 03:34:17 · answer #7 · answered by sugar 2 · 0 0

2+2=4
(67+78)=145
30-1+29
4(145)29
=16820

=)

2006-11-02 04:37:06 · answer #8 · answered by ♥ mars♥ 4 · 0 1

8701

2006-11-02 04:40:07 · answer #9 · answered by Anonymous · 0 0

8701

2006-11-02 03:40:03 · answer #10 · answered by ddudley543 2 · 0 0

8701

2006-11-02 03:38:08 · answer #11 · answered by csulbalgebra 2 · 0 0

fedest.com, questions and answers